2017
DOI: 10.26451/abc.04.03.13.2017
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study to investigate the Delboeuf illusion in ring-tailed lemurs (Lemur catta): Methodological Challenges

Abstract: -Visual illusions are commonly used in animal cognition studies to compare visual perception among vertebrates. To date, researchers have focused their attention mainly on birds and mammals, especially apes and monkeys, but no study has investigated sensitivity to visual illusions in prosimians. Here we investigated whether lemurs (Lemur catta) perceive the Delboeuf illusion, a well-known illusion that occurs when subjects misperceive the relative size of an item because of its surrounding context. In particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
(46 reference statements)
0
25
0
Order By: Relevance
“…These findings regarding the control performance suggest that dogs, as individuals, failed to reliably select the larger portion of food, and therefore, the results in the illusion condition must be interpreted with caution. While the findings observed in the spontaneous choice paradigm parallel those observed in a trained two-choice discrimination paradigm (Byosiere et al, 2016), the findings are limited by the levels of individual success on control conditions (for a detailed account of limitations in spontaneous choice tasks, see Santacà, Regaiolli, Miletto Petrazzini, Spiezio, & Agrillo, 2017). It also suggests that care should be taken when using a spontaneous choice paradigm as results in the test condition, when the illusion is presented, are largely uninterpretable if poor performance in the controls trials is observed.…”
Section: Ebbinghaus-titchener and Delboeuf Illusionsmentioning
confidence: 64%
“…These findings regarding the control performance suggest that dogs, as individuals, failed to reliably select the larger portion of food, and therefore, the results in the illusion condition must be interpreted with caution. While the findings observed in the spontaneous choice paradigm parallel those observed in a trained two-choice discrimination paradigm (Byosiere et al, 2016), the findings are limited by the levels of individual success on control conditions (for a detailed account of limitations in spontaneous choice tasks, see Santacà, Regaiolli, Miletto Petrazzini, Spiezio, & Agrillo, 2017). It also suggests that care should be taken when using a spontaneous choice paradigm as results in the test condition, when the illusion is presented, are largely uninterpretable if poor performance in the controls trials is observed.…”
Section: Ebbinghaus-titchener and Delboeuf Illusionsmentioning
confidence: 64%
“…We adapted a procedure used in research on other mammals [23][24][25][26] that consists of the observation of the spontaneous preference of the animals for reaching the largest amount of food. In control trials, we presented subjects with two portions that differed in size.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study assessing susceptibility to the Ebbinghaus-Titchener illusion, reversed susceptibility was found in this same group of dogs when presented with two different illusory contexts , and two studies have failed to observe canine susceptibility to the Delboeuf illusion Miletto Petrazzini et al, 2017). Baboons, the only other terrestrial species to have been assessed on the Ebbinghaus-Titchener illusion, failed to demonstrate susceptibility to the illusion (Barbet & Fagot, 2002), and while some terrestrial species, such as chimpanzees, macaques and capuchin monkeys Parrish, Brosnan, & Beran, 2015), have demonstrated human-like susceptibility to the Delboeuf illusion, others, like ring-tailed lemurs, have not (Santacà et al, 2017). Yet, it is important to note that these studies emphasize the methodological constraints and confounds that arise when evaluating illusion susceptibility in animals.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, it is important to note that these studies emphasize the methodological constraints and confounds that arise when evaluating illusion susceptibility in animals. Presentation style, training procedures, stimuli design, the kind of paradigm used, and failure to reliably differentiate control stimuli have all been observed to affect the perception of the Ebbinghaus-Titchener and Delboeuf illusions in animals (Barbet & Fagot, 2002;Parrish et al, 2015;Santacà et al, 2017). Future research should examine vertical Ponzo illusion susceptibility using additional pictorial linear perspective cues, as has been done in horses (Timney & Keil, 1996), or within alternative testing paradigms (e.g., absolute classification, same-different tasks).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation